Eksplorasi Media Bahan Alam untuk Meningkatkan Kreativitas Seni Pada Anak Usia 5-6 Tahun - A'la Rahmatin Nawangsari; Diana Dwi Jayanti; Dina Fitriana; Dinar M. Leksana; Imas Jihansyah (JCE (Journal of Childhood Education), 2025)
This study investigated the effectiveness of exploring natural materials as media to enhance artistic creativity in 5-6-year-old children at TK Pembangunan Glagah Lamongan. A pre-experimental quantitative approach with a one-group pre-test post-test design was employed. The study's subjects comprised 13 students from Group B at TK Pembangunan Glagah Lamongan, selected using a saturated sampling technique. Primary data were collected through a validated and reliable observation instrument, while secondary data were obtained via field observations and interviews conducted throughout the study. Data analysis was performed using the Wilcoxon Signed-Rank Test to determine significant differences between pre-test and post-test scores of children's artistic creativity, with a significance level of 0.05. The Wilcoxon Signed-Rank Test results, with a p-value of 0.002, indicate that the use of natural materials as media significantly improved artistic creativity in 5-6-year-old children at TK Pembangunan Glagah Lamongan. This intervention successfully enhanced creativity in most students without diminishing it in others.